2007
DOI: 10.1158/1535-7163.mct-06-0605
|View full text |Cite
|
Sign up to set email alerts
|

Emodin has a cytotoxic activity against human multiple myeloma as a Janus-activated kinase 2 inhibitor

Abstract: Emodin is an active component of a traditional Chinese and Japanese medicine isolated from the root and rhizomes of Rheum palmatum L. Here, we show that emodin significantly induces cytotoxicity in the human myeloma cells through the elimination of myeloid cell leukemia 1 (Mcl-1). Emodin inhibited interleukin-6 -induced activation of Janus-activated kinase 2 (JAK2) and phosphorylation of signal transducer and activator of transcription 3 (STAT3), followed by the decreased expression of Mcl-1. Activation of cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 52 publications
5
76
0
1
Order By: Relevance
“…It also promotes the apoptosis of human breast cancer BCap-37 cells . Some studies have also reported the effect of emodin on cell death in human prostate, lung, liver, cervical and blood cancer cells (Cha et al, 2005;Su et al, 2005;Jing et al, 2006;Fu et al, 2007;Muto et al, 2007). In this study, compound 5 (emodin) and ampicillin acted jointly against P. aeruginosa more effectively than either of them did alone, suggesting that compound 5 enhanced the activity of ampicillin against P. aeruginosa.…”
Section: Discussionsupporting
confidence: 55%
“…It also promotes the apoptosis of human breast cancer BCap-37 cells . Some studies have also reported the effect of emodin on cell death in human prostate, lung, liver, cervical and blood cancer cells (Cha et al, 2005;Su et al, 2005;Jing et al, 2006;Fu et al, 2007;Muto et al, 2007). In this study, compound 5 (emodin) and ampicillin acted jointly against P. aeruginosa more effectively than either of them did alone, suggesting that compound 5 enhanced the activity of ampicillin against P. aeruginosa.…”
Section: Discussionsupporting
confidence: 55%
“…This EM has been used as a traditional oriental medicine for the treatment of skin burn, infection, gallstone, hepatitis, inflammation, and osteomyelitis. Moreover, this is a safe agent even in long exposure in mice (Muto et al, 2007). Hatano et al (1999) reported that EM, aloe-emodin, and the others, showed strong antibacterial activity against MRSA.…”
Section: Discussionmentioning
confidence: 94%
“…Emodin is a potent inhibitor of casein kinase 2 (CK2), which regulates JAK/STAT signaling (55). Furthermore, emodin has been shown to directly inhibit JAK activity (56). Emodin has also been reported to be an agonist for PPAR␥ (51).…”
Section: Discussionmentioning
confidence: 99%